Criminal-Legal Protection of Copyright - Jovašević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
Since 2006, when new criminal legislation came into force, and 2009, when new copyright legislation came into force, the level of individual, collective and criminal – legal protection of copyright and related rights has been upgraded in a qualitative sense. Following other comparative legislations as role models, as well as the standards proclaimed by international legal documents, the Criminal Code categorized (for the first time in our country) all criminal offences representing violations or endangerments of copyright and related rights (that are covered by the term "intellectual property rights") in a separate chapter (Chapter 20) entitled as: "Criminal Offences against Intellectual Property". New legislative solutions are based upon the provisions of the new Law on Copyright and Related Rights adopted in 2009. This paper discusses the definition, the characteristics and the features of the most significant criminal offence by which copyright and related rights (material as well as immaterial or moral rights) are violated or endangered - Unauthorized Use of Copyrighted Work or other Work Protected by Similar Right (from Paragraph 199 of the Criminal Code) from theoretical as well as from practical aspects.